Key for the identification of the instars of the English grain aphid, Sitobion αvenαe (F.) (Hemiptera: Aphididae) - Lykouressis D.Ρ (ENTOMOLOGIA HELLENICA, 1983)
A key is given for the identification of the instars of the English grain aphid, Sitobion avenae (F.) based upon morphological characters of the antennae, cauda and sub-anal plate.